Dental procedures in 24 patients with chronic immune thrombocytopenia in prospective clinical studies of eltrombopag. (February 2015) - Tarantino, Michael D.; Fogarty, Patrick F.; Shah, Palvi; Brainsky, Andrés
Abstract Primary immune thrombocytopenia (ITP) is an autoimmune disease characterized by chronically low peripheral blood platelet counts. Eltrombopag is an oral, non-peptide, thrombopoietin-receptor agonist that increases platelet production. This report examines peri-procedural platelet counts and bleeding complications among chronic ITP patients requiring dental procedures while participating in clinical studies with eltrombopag. A total of 494 patients participated in five clinical studies of eltrombopag in chronic ITP. Information about dental procedures was collected prospectively in four studies and retrospectively in one study. Twenty-four patients (22 eltrombopag, 2 placebo) underwent 32 dental procedures (dental cleaning, tooth repair, artificial crown, dental prosthesis, tooth extraction, dental or wisdom teeth extraction, dental root extraction, and endodontic procedures, among others) during study treatment or up to 10 days later. Supplemental ITP therapy (e.g., corticosteroids, platelet transfusions) was given before the dental procedure to increase platelet counts in three eltrombopag-treated patients and both placebo-treated patients. The mean pre-procedure platelet count ± standard deviation for all procedures in the overall population of patients, eltrombopag group, and placebo group prior to undergoing dental procedures was 96 000 ± 81 069/µl, 103 517 ± 81 522/µl, and 23 333 ± 9291/µl, respectively. Two patients in each group had platelet counts below 30 000/µl before the procedure. No patient who had a dental procedure experienced a bleeding adverse event. Among patients with chronic ITP who required a dental procedure during clinical studies of eltrombopag, supplemental ITP treatment was required for both patients who received placebo but was not required for most patients who received eltrombopag. No bleeding complications were reported. These data imply that patients with chronic ITP who receive eltrombopag and experience increases in platelet counts fulfill current pre-procedural platelet count recommendations to undergo invasive dental procedures, and may have a lower risk of bleeding complications and a reduced need for supplemental ITP treatment.